Pemilihan Lokasi Prioritas Pelayanan Sistem Penyaluran Air Limbah Domestik Setempat di Kecamatan Purwasari Dengan Metode Skoring dan Pembobotan - Hartati, Etih; Aditya Pratama (Jurnal Serambi Engineering, 2025)
Rapid population growth in Indonesia, particularly in Karawang Regency, has put additional pressure on infrastructure and the environment, including an increase in the volume of domestic wastewater. This has led to water pollution, which poses a risk to public health, such as waterborne diseases. This issue is critical to efforts to achieve the 2030 Sustainable Development Goals (SDGs), particularly SDG 6, which targets access to adequate sanitation and sustainable water management. The local government of Karawang Regency, through the 2011-2031 Spatial Plan (RTRW) and the 2021-2026 Regional Medium Term Development Plan (RPJMD), plans to develop municipal wastewater treatment plants (IPAL) and sewerage systems in each district, including Purwasari District. The purpose of this study is to plan a domestic sanitation system in Purwasari District to reduce water pollution and improve access to adequate sanitation. The method used in this study is a scoring and weighting technique to assess the capacity of each parameter relevant to domestic sanitation. The results of the study show that Darawolong and Karangsari villages in Purwasari district are prioritised in the planning of the Local Domestic Sanitation System (SPALD-S) due to their higher urgency. The development of SPALD-S in these two villages is expected to bring long term benefits in terms of improved sanitation and environmental health for the local community.